2021
DOI: 10.1016/j.infpip.2021.100126
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial contamination of mobile phones of healthcare workers at the University Teaching Hospital, Lusaka, Zambia

Abstract: Summary Background Mobile telephones (henceforth ‘phones’) have become an essential part of everyday life in both healthcare and community settings. However, the widespread use of mobile phones in healthcare facilities is of concern because they can act as vehicles for transmitting pathogenic bacteria. This study aimed to investigate the bacterial contamination of mobile phones of healthcare workers (HCWs) at the University Teaching Hospital, Lusaka, Zambia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 38 publications
4
35
1
1
Order By: Relevance
“…Antibiotic-resistant bacteria are the most serious health risk for patients. 32 Most of the isolates (88.1%) in this study were resistant to at least one antibiotic tested. Bacterial isolates showed a higher resistance rate against penicillin (84%) followed by ampicillin (81%) and tetracycline (42%), Also, MRSA and methicillin-resistant CoNS were isolated.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Antibiotic-resistant bacteria are the most serious health risk for patients. 32 Most of the isolates (88.1%) in this study were resistant to at least one antibiotic tested. Bacterial isolates showed a higher resistance rate against penicillin (84%) followed by ampicillin (81%) and tetracycline (42%), Also, MRSA and methicillin-resistant CoNS were isolated.…”
Section: Discussionmentioning
confidence: 70%
“…This is opposite to other similar studies done in Zambia. 32 This difference might be the reflection of poor adherence to the infection prevention practice in ICU of the present study area. The rate of bacterial contamination of MP owed by those HCWs who did not disinfect or clean their phone was also higher than those who cleaned their phone.…”
Section: Discussionmentioning
confidence: 75%
“…Healthcare workers’ mobile phones can also be a source of transmission of resistant bacteria to the community ( Debnath et al, 2018 ; Mushabati et al, 2021 ). In EU, this problem seems to be less striking with fewer resistant bacteria detected on the phones ( Galazzi et al, 2019 ; Missri et al, 2019 ).…”
Section: Prevention Of Infectionmentioning
confidence: 99%
“…10 Various studies in different medical institutions have reported that 71.8-100% of healthcare workers' mobile phones are contaminated with organisms, including Gram-positive and Gram-negative bacteria and fungi. [11][12][13][14][15][16][17][18] Furthermore, studies have shown that bacteria isolated from mobile phones are MDR. 19 A study carried out in Ethiopia found an overall prevalence of 69.9% MDR bacterial isolates.…”
Section: Introductionmentioning
confidence: 99%